2022
DOI: 10.1038/s41467-022-33809-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of cyanate anion from dinitrogen catalysed by molybdenum complexes bearing pincer-type ligand

Abstract: Dinitrogen is an abundant and promising material for valuable organonitrogen compounds containing carbon–nitrogen bonds. Direct synthetic methods for preparing organonitrogen compounds from dinitrogen as a starting reagent under mild reaction conditions give insight into the sustainable production of valuable organonitrogen compounds with reduced fossil fuel consumption. Here we report the catalytic reaction for the formation of cyanate anion (NCO−) from dinitrogen under ambient reaction conditions. A molybden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…As described in here, we consider that the use of the BDFE(N-H) values of key reactive intermediates, such as molybdenum-imide, molybdenum-amide and molybdenum-ammine complexes estimated by DFT calculations provides a suitable and reliable predicting method to develop more effective catalysts under ambient reaction conditions. The catalysts successfully developed will be applied not only to the catalytic nitrogen fixation driven by visible light 62 and electrochemical energy, but also to the catalytic formation of nitrogen-containing organic compounds directly from nitrogen gas under mild reaction conditions 63 . We believe that these findings can contribute to the development of an environmentally friendly next-generation nitrogen-fixation system in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…As described in here, we consider that the use of the BDFE(N-H) values of key reactive intermediates, such as molybdenum-imide, molybdenum-amide and molybdenum-ammine complexes estimated by DFT calculations provides a suitable and reliable predicting method to develop more effective catalysts under ambient reaction conditions. The catalysts successfully developed will be applied not only to the catalytic nitrogen fixation driven by visible light 62 and electrochemical energy, but also to the catalytic formation of nitrogen-containing organic compounds directly from nitrogen gas under mild reaction conditions 63 . We believe that these findings can contribute to the development of an environmentally friendly next-generation nitrogen-fixation system in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This goal first began in the 1960s, when Vol’pin synthesized aniline from dinitrogen by reacting titanium salts with PhLi under a dinitrogen atmosphere . Most recently, Nishibayashi et al provided the first successful example of the catalytic transformation of N 2 to NCO – under ambient reaction conditions . Holland et al reported a remarkable milestone to carry out N 2 coupling with arene to generate aniline by the key step of aryl group migration to the partial silylated iron-dinitrogen complex (Figure B) …”
Section: Introductionmentioning
confidence: 99%
“…9 Most recently, Nishibayashi et al provided the first successful example of the catalytic transformation of N 2 to NCO − under ambient reaction conditions. 10 Holland et al reported a remarkable milestone to carry out N 2 coupling with arene to generate aniline by the key step of aryl group migration to the partial silylated irondinitrogen complex (Figure 1B). 11 N 2 activation and direct insertion into a non-activated aliphatic Csp 3 −H bond to form an aliphatic C−N bond seems a very challenging goal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In principle, the addition of an activated N 2 unit to unsaturated organic substrates could offer an atom-efficient route for the synthesis of organonitrogen compounds. However, studies toward this goal remained limited despite great interest and recent advances. The nucleophilic addition of N 2 or N 2 -derived nitrido and imido species to unsaturated carbon-heteroatom bonds such as CO, CO 2 , ,, aldehydes/ketones, acid halides, nitriles, , and heteroallenes ,,,, has been reported. However, the addition reaction of N 2 with unsaturated C–C bonds has remained almost unexplored to date. , In particular, the addition of an N 2 unit to an α,β-unsaturated carbonyl compound through the C–N bond formation to produce an NN-functionalized organic compound has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%